Islamic Education in The Family in The Digital Age: Challenges and Solutions - Rahman, Abd. (Teunuleh Publisher, 2025)
The digital era has significantly transformed various aspects of life, including Islamic education within the family. This study examines how Muslim families navigate the challenges and opportunities of raising children in the digital age. Using a qualitative approach and descriptive analysis of relevant literature, the findings reveal that digitalization facilitates access to Islamic learning resources, such as e-books, online lectures, and educational apps. However, challenges include exposure to un-Islamic digital content, gadget addiction, and reduced face-to-face family interaction. To address these issues, Muslim families can adopt strategies like monitoring technology use, leveraging positive digital media, and integrating Islamic values into parenting. The study highlights the crucial role of parents as facilitators in guiding children to use technology wisely and in line with Islamic principles. Additionally, Islamic educational institutions and policymakers should contribute by establishing regulations and educational programs that promote healthy technology use in family-based Islamic education. For future research, empirical studies using quantitative or in-depth qualitative methods are recommended to explore digital-based Islamic education across diverse cultural and social contexts. Further evaluation of technology-driven Islamic learning methods is also needed to provide more specific and actionable recommendations.